PENGEMBANGAN MODUL TEMATIK BERBASIS 4C MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING KELAS 3 SUBTEMA 3 - Yulianti Yulianti; Nova Tutianingsih (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
This study aims to develop a product in the form of a 4C-based Thematic Module through a Contextual Teaching And Learning (CTL) Approach Class 3 Subtema 3 that is feasible and practical. This research is a type of product-oriented development research. The model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation) which is modified from 5 stages to 4 stages. Validation was carried out by module experts as well as material and language experts, practicality by teachers and field trials were limited to 8 students of SDN 3 Srigonco. The results of the study were 91% of module experts, 91% of material and Â language experts, which meant "very valid", 88% of practicality from teachers and 88% of students' meaning "very good". It is hoped that further research can develop this product by adding learning and subthemes and testing its effectiveness to improve student learning outcomes.Keywords: Thematic Module, 4C, CTLÂ